Analisis Bahasa Pemrograman Java dengan Bahasa Pemrograman Visual Basic Program Aplikasi Perkalian Matriks - Fajar Shodik; Arnellis Arnellis (Journal of Mathematics UNP, 2021)
The rapid development of Information Technology today brings ease of work in variousfields, such as mathematics. Complex calculations can be completed easily and quickly just by using acalculator.  Calculations  can  also  be  done  using  an  application  program,  where  the  application  isdeveloped  using  a  programming  language.  Of  the  many  programming  languages  that  exist  today,including Java and VisualBasic. This research is a basic research where in this study an analysis of the programming language with matrix multiplication problems is carried out.The purpose oft his research is to see which programming language is better based on predetermined criteria. The research methodused  is  by  analyzing  the  algorithms  of  the  two  programming  languages  with  matrix  multiplicationproblems  based  on  relevant  sources.  The  results  showed  that  the  Visual Basic  is  better  than  the  Java based on these criteria.